Pengembangan Budaya Kewirausahaan Berbasis Syariah dalam Menumbuhkan Jiwa Entrepreneurship Santri pada Pondok Pesantren Ma’had Mambaul Hikam (MMH) Jombang - Makrifatul Ilmi (LP3M STITNU Al Hikmah Mojokerto, 2019)
Islamic boarding schools are one of the many educational institutions in Indonesia, so this institution participates in advancing human resources. Entrepreneurial ability is one of the things that must be intensified in Islamic boarding school educational institutions, the aim being that the santri is not only able to apply religious knowledge but also able to create jobs. This will contribute a great deal in economic life, especially in creating entrepreneurs from the santri environment, who have characteristics that are full of honesty, tenacious, independent and never give up. For this reason, this study is focused on the Development of a Sharia-Based Entrepreneurship Culture in Growing the Entrepreneurship of Santri at the Mambaul Hikam Jombang Islamic Boarding School.